3Sesi Pelajar KUTKM Berbuka Bersama Rektor - Safei, Su'aidi (KUTKM, 2004)
Office of Students Affair (HEP) in collaboration with the Student Representative Council (MPP) continued the regular practice of dining delicacies of  breaking of fast with the Rector of the university students for three consecutive days in conjunction with Ramadan mubarak. The program managed to reach between leaders and students, and thus making this interaction something meaningful.